FTY720 controls disease severity and attenuates sciatic nerve damage in chronic experimental autoimmune neuritis - Laurent Kremer; Omar Taleb; Nelly Boehm; Ayikoe Guy Mensah-Nyagan; Elisabeth Trifilieff; Jérôme de Seze; Susana Brun (Journal of Neuroinflammation, 2019)
Abstract Background Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an autoimmune-mediated inflammatory disease of the peripheral nervous system characterized by a response directed against certain myelin proteins and for which therapies are limited. Previous studies have suggested a beneficial role of FTY720, a sphingosine 1-phosphate (S1P) receptor agonist, known to deplete lymphocytes from the peripheral blood by sequestering them into lymph nodes, in the treatment of experimental autoimmune neuritis (EAN). Therefore, we investigated whether FTY720 is also beneficial in chronic experimental autoimmune neuritis (c-EAN), a recently developed rat model mimicking human CIDP. Methods c-EAN was induced in Lewis rats by immunization with S-palm P0(180–199) peptide. Rats were treated with FTY720 (1 mg/kg) or vehicle intraperitoneally once daily from the onset of clinical signs for 18 days; clinical signs were assessed daily until 60 days post-immunization (dpi). Electrophysiological and histological features were examined at different time points. We also evaluated the serum levels of different pro- and anti-inflammatory cytokines by ELISA or flow cytometry at 18, 40, and 60 dpi. Results Our data demonstrate that FTY720 decreased the severity and abolished the chronicity of the disease in c-EAN rats. Therapeutic FTY720 treatment reversed electrophysiological and histological anomalies, suggesting that myelinated fibers were subsequently preserved, it inhibited macrophage and IL-17+ cell infiltration in PNS, and it significantly reduced circulating pro-inflammatory cytokines. Conclusions FTY720 treatment has beneficial effects on c-EAN, a new animal model mimicking human CIDP. We have shown that FTY720 is an effective immunomodulatory agent, improving the disease course of c-EAN, preserving the myelinated fibers, attenuating the axonal degeneration, and decreasing the number of infiltrated inflammatory cells in peripheral nerves. These data confirm the interest of testing FTY720 or molecules targeting S1P in human peripheral neuropathies.